Who is considered "foreign": Ethnic stereotypes in press releases across Europe - Tobias Heidenreich; Olga Eisele (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2023)
How do political elites talk about immigrants and refugees? Tobias Heidenreich and Olga Eisele examined almost 100,000 press releases from governments in four countries and from the EU itself. Their finding: There are big differences in who is associated with "high threat" or "low status". But this can have major consequences for the individual groups and for the public opinion.
Keywords: 300